2005
DOI: 10.5551/jat.12.205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atorvastatin on Regional Arterial Stiffness in Patients with Type 2 Diabetes Mellitus

Abstract: Objective: A statin, a potent lipid-lowering drug, improves pain-free walking distance in patients with peripheral arterial disease (PAD) without increasing the ankle-brachial pressure index (ABI). Arterial stiffness affects the blood flow of peripheral arteries. The purpose of this study was to evaluate the effect of cholesterol-lowering with atorvastatin on regional arterial stiffness in patients with type 2 diabetes mellitus. Methods: The subjects were 22 type 2 diabetic patients with hypercholesterolemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 32 publications
1
53
1
3
Order By: Relevance
“…In our subjects treated with lipid-lowering medications (n 795), 648 patients were on statin treatment. PWV of the leg arteries, but not of the central arteries, showed a significant decrease during longitudinal observations with simvastatin 19) or atorvastatin 21) . Although the present finding was based on cross-sectional analysis, the observed inverse association between lipid-lowering medication and faPWV is in good agreement with longitudinal studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our subjects treated with lipid-lowering medications (n 795), 648 patients were on statin treatment. PWV of the leg arteries, but not of the central arteries, showed a significant decrease during longitudinal observations with simvastatin 19) or atorvastatin 21) . Although the present finding was based on cross-sectional analysis, the observed inverse association between lipid-lowering medication and faPWV is in good agreement with longitudinal studies.…”
Section: Discussionmentioning
confidence: 98%
“…A very recent report by Tanaka et al 16) showed that baPWV and carotid-femoral PWV were closely and comparably associated with blood pressure, the Framingham risk score (FRS), and pre-existing CVD. Previous studies [17][18][19][20][21][22] showed that the impact of some CVD risk factors and medications on PWV varies among different arterial territories. Also, the association of pre-existing CVD with PWV appears to vary among these regional PWV measurements [23][24][25] ; therefore, it is an important question whether baPWV is an index of central or peripheral arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, clinical studies indicated that intervention with metformin, ACE inhibitors, angiotensin receptor blockers or alpha-lipoic acid would be able to reduce the levels of circulating ADMA [49][50][51][52][53][54][55] . The bibliography on the efficacy of statins on ADMA is contentious [20,[56][57][58][59][60][61] . Meanwhile, one clinical study demonstrated an ADMA decrease during intervention with rosiglitazone, and this was not recognized in a discrete age group [62,63] .…”
Section: Our Experience With Admamentioning
confidence: 99%
“…ABI was measured using a method described elsewhere [22][23][24] . Briefly, the patient remained still in the supine position for 5 minutes, and a cuff for blood pressure measurement was then applied to both arms and legs.…”
Section: Measurement Of Transcutaneous Oxygen Tension (Tcpo2) and Ankmentioning
confidence: 99%